Exploring pre-impact landing kinematics associated with increase and decrease in the anterior cruciate ligament injury risk - Wakabayashi, K.; Ogasawara, I.; Suzuki, Y.; Nakata, K.; Nomura, T. (Journal of Biomechanics, 2022)
This study aimed to explore the single-legged landing kinematics that could lead to increase or decrease in the risk of anterior cruciate ligament (ACL) injury. Immediate pre-impact kinematics at the single-legged landing from 33 healthy young female handball players were evaluated. Thereafter, two-year follow-up for ACL injury incidence was conducted, in which six new ACL injuries in non-dominant leg were registered. The evaluation of pre-impact kinematics across participants was performed first by the principal component analysis to decompose them into the kinematic components (KCs), and then by the linear discrimination analysis (LDA) for a set of KC-scores to obtain important KCs for discriminating injured and non-injured legs. The result of LDA showed that the combination of second major KC (knee flexion/extension angle and angular velocity) and some minor KCs such as torso medial/lateral leaning accurately discriminated the injured and non-injured legs with the error rate of 12.5%. To examine the mechanisms of this discriminative ability, we generated hypothetical pre-impact kinematics in the subspaces spanned by eigenvectors of multiple KCs, and examined relationships between pre-impact kinematics and the corresponding knee valgus torque predicted by the motion-equation-based model. The result showed that the second major KC and the minor KCs representing torso medial/lateral leaning and/or hip adduction/abduction angle, which contributed in LDA to discriminating injured legs, also significantly affected the frontal-plane knee loading patterns. These findings suggested that KC-based postural characterization of the pre-impact landing kinematics and the motion-equation-based knee stress quantification possibly explain the future ACL injury risks of female athletes.